Characterizations of commiphora gileadensis plant: A review and future trends - Aiman A., Mokaizh; Nour, Abdurahman Hamid; R. M., Yunus; Norasyikin, Ismail; Hawege, Emsalem Faraj (AIP Publishing, 2024)
Since Ancient times, Commiphora gileadensis has been used to treat a variety of illnesses, and it is still utilised in several Middle Eastern countries’ traditional medicine today. There is a lack of data on the leaf and stem extracts of C. gileadensis’s phytochemical and structural qualities. The purpose of this review is to highlight the analyses that were carried out to characterise the C. gileadensis extract and to point out their results. The method used in this study is focused on a thorough search of the literature, and data from book chapters, research articles, review articles, and conference papers was used. The obtained results of the search to investigate the C. gileadensis genus were including the of using Fourier-Transform Infrared Spectroscopy (FTIR), Gas Chromatography–Mass Spectrometry (GC-MS), Liquid Chromatography–Mass Spectrometry (LC–MS), and Nuclear Magnetic Resonance (NMR). Overall, the findings of the characterizations showed that C. gileadensis included phenolic compounds, which can be a significant natural antioxidant source for therapeutic applications. The future trends include the suggestions for conducting more characterizations such as Liquid chromatography-mass spectrometry-quadrupole time-of-flight (LC-Q-TOF-MS), Inductively coupled plasma-mass spectrometry (ICP-MS).